Before the Battle Begins: Primary Vote and the 2019 Election - chaiyapon, chaiyan; thananithichot, stithorn (King Prajadhipok’s Institute Journal, 2020)
This article aims to analyze the extent to which the Constitution of the Kingdom of Thailand, B.E. 2560 [2017] and the Organic Act on Political Parties, B.E. 2560 [2017] have brought about reform of political parties. To achieve this goal, this article used a conceptual framework derived from the theory of mixed constitution and the methodology of qualitative research. The study revealed that despite some political parties’ efforts to increase space for their members to participate in certain activities,especially those concerning candidate selection, most political parties are still subject to manipulation by the party leader and party executive members. Thus, it cannot be said that the expansion of party members’ participation in parties’ political affairs has been the practical outcome of the Organic Act on Political Parties. Rather, evidence from many cases revealed that increases in the number of a political party’s members and any broadening of their roles occurred due to an attempt to adapt to electoral competition conditions under the new electoral system mandated in the constitution and political party law. Therefore, this article suggests that political party laws concerning the process of candidate selection within the political party should be practical and written in ways that support members of political parties to participate in all of their parties’ processes and activities meaningfully and voluntarily, instead of the current strict legislation that is too difficult to implement and does not help to increase the power of political party members.